RETRACTED: An Efficient Ultrasound-Assisted Synthesis of Cu/Zn Hybrid MOF Nanostructures With High Microbial Strain Performance - Abdieva, Gulnora Abdullaevna; Patra, Indrajit; Al-Qargholi, Basim; Shahryari, Taher; Chauhan, Narendra Pal Singh; Moghaddam-manesh, Mohammadreza (Frontiers in Bioengineering and Biotechnology, 2022)
Metal organic frameworks (MOFs) are a promising choice for antibacterial and antifungal activity due to their composition, unique architecture, and larger surface area. Herein, the ultrasonic method was used to synthesize the Cu/Zn-MOF material as an effective hybrid nanostructure with ideal properties. SEM images were used to investigate the product’s morphology and particle size distribution. The XRD pattern revealed that the Cu/Zn hybrid MOF nanostructures had a smaller crystalline size distribution than pure Cu and Zn-MOF samples. Furthermore, the BET technique determined that the hybrid MOF nanostructures had a high specific surface area. TG analysis revealed that the hybrid MOF structures were more thermally stable than pure samples. The final product, with remarkable properties, was used as a new option in the field of antibacterial studies. Antibacterial activity was assessed using MIC and MBC against Gram negative and Gram positive strains, as well as antifungal activity using MIC and MFC. The antimicrobial properties of the synthesized Cu/Zn hybrid MOF nanostructures revealed that they were more effective than commercial drugs in some cases. This study’s protocol could be a new strategy for introducing new hybrid nanostructures with specific applications.